The Role of the State in the Management of Zakat in Indonesia - Hafzi, Ahmad; Ikhwan, Ikhwan; Marneli, Marneli (Universitas Islam Negeri Sumatera Utara, 2024)
Zakat is one of the pillars of Islam that is implemented based on Islamic law. Zakat is not only considered as a ritual worship, but also a social worship that has political aspects due to the involvement of the state in managing it. Since the time of Prophet Muhammad sallallahu